2019
DOI: 10.2147/ott.s198567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Decitabine enhances cytotoxic effect of T cells with an anti-CD19 chimeric antigen receptor in treatment of lymphoma</p>

Abstract: Background: CD19-directed chimeric antigen receptor (CAR) T cells have substantial benefit in the treatment of patients with B-cell malignancies. However, despite encouraging therapeutic efficiency, there is limited overall response rate when anti-CD19 CAR-T cells are used to treat patients with relapsed and refractory (R/R) B cell lymphomas. Therefore, it further investigation is urgently needed to improve treatment efficacy. Method: A combined treatment protocol of CAR-T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“… 32 Another demethylating agent, decitabine, was shown to increase the expression of CD19 on lymphoma cells and enhanced the cytotoxic effect of CAR19 T cells. 35 In our experiments, however, AZA did not up-regulate CD19 cell surface expression in B-ALL cells. Additionally, neither PD-L1/PD-L2 expression in leukemia cells nor PD-1 expression in CAR T cells was affected by pre-treatment of leukemia/hosts with AZA, suggesting that AZA effects were not mediated through the modulation of the inhibitory PD-1 checkpoint.…”
Section: Discussioncontrasting
confidence: 63%
“… 32 Another demethylating agent, decitabine, was shown to increase the expression of CD19 on lymphoma cells and enhanced the cytotoxic effect of CAR19 T cells. 35 In our experiments, however, AZA did not up-regulate CD19 cell surface expression in B-ALL cells. Additionally, neither PD-L1/PD-L2 expression in leukemia cells nor PD-1 expression in CAR T cells was affected by pre-treatment of leukemia/hosts with AZA, suggesting that AZA effects were not mediated through the modulation of the inhibitory PD-1 checkpoint.…”
Section: Discussioncontrasting
confidence: 63%
“…The results of this clinic trial demonstrate decitabine is modestly safe and active, and has a potential synergistic effect with chemotherapy in obstinate R/R-DLBCL. Along with the deep exploration of lymphoma therapy, DAC increases expression of the surface antigen CD19 on lymphoma cells and potentiates the activity of CAR-T cells towards B-cell malignancies (40). The ORR and CR rates of relapsed/refractory cHL patients who received decitabine plus PD-1 blockade was significantly higher than those who took PD-1 blockade alone.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated for the first time that pretreatment with DAC augments activation of CD123 CAR-T cells in vitro and also show an enhanced antileukemia effect in the context of combination treatment in vivo. Consistent with these results, Li et al (20) reported that lymphoma cells were more sensitive to killing by CD19 CAR-T cells following pretreatment with DAC, and that two patients with refractory/relapsed B-cell lymphoma received sequential therapy (DAC followed by CAR-T cells), of whom both achieved CR. Together, these data may indicate the FIGURE 4 | Investigations on the effect of DAC on intrinsic potency and subsets of CAR-T cells.…”
Section: Discussionmentioning
confidence: 59%